The Effect of Self-Management On Therapy Compliance To Improve The Quality of Life of Type 2 Diabetes Mellitus Patients At The UPTD Diabetes Center In Ternate City, Indonesia - Nursia Aja; Ismawanti Sawedi; Diah Ariana; Dzul Akmal (International Journal of Health and Pharmaceutical (IJHP), 2025)
Diabetes Mellitus (DM) is a metabolic disease characterized by high blood glucose levels as a result of insufficient insulin secretion, impaired insulin activity, or both. The purpose of this study was to determine and analyze the effect of self-management on the level of therapy adherence, as well as its impact on improving the quality of life of Type 2 Diabetes Mellitus sufferers. The design in this study is descriptive, the effect of Self-Management on therapy adherence to improve the quality of life of Type 2 Diabetes Mellitus sufferers with a cross-sectional research method was carried out at the same time without a follow-up period. The population in the study at the UPTD Diabetes Center Ternate City in 2024 who suffered from DM was 92 people. The sampling technique used in this study was total sampling, namely all DM sufferers who were treated and registered at the UPTD Diabetes Center in 2024 as many as 92 people. The results of the study showed that there was a significant relationship between the level of knowledge (p = < 0.000), the level of self-management ability (p = <0.000) with Type 2 Diabetes Mellitus sufferers. While the variables of therapy compliance (p = > 1.000) and improving the quality of life were not significantly related, namely (p = > 0.311) with Type 2 Diabetes Mellitus sufferers. Nurses can improve patient knowledge by providing education that focuses on improving self-management and providing therapy compliance and improving the quality of life of Type 2 Diabetes Mellitus sufferers.